CROSS CULTURE UNDERSTANDING IN EFL TEACHING: AN ANALYSIS FOR INDONESIA CONTEXT - MAULANA, ANDRI (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2020)
This study attempts to elaborate on the importance of cultural understanding of English foreign learners’ communicative competence. In the English language teaching in Indonesia, the role of culture is a crucial thing which needs to be combined with the teaching material to assist teachers and students for reaching the learning objective. Based on the findings of some studies, English learners in Indonesia face several obstacles when they find some terms which are unable to get its point in the literal meaning. Understanding the background culture in learning English is expected to minimize students' misunderstanding and lead them to use proper English in real communication. Integrated teaching material which contains cultural contents and its backgrounds is one way to introduce English to the learners, not only as a language but as a culture as well. Providing topics of learning based on authentic sources from native English speaking countries such as fable, short story, conversation role-play, songs, and movie. Arranging integrated teaching material that covers listening, speaking, reading, and writing with included cultural or arts contents of English native speakers. The teacher should not only teach students in linguistic competence but should teach them communicative competence as well because mastering linguistic competence is insufficient to use English in natural discourse. The appropriateness of English in use toward communication context is the objective of understanding the culture and language.Keywords: Culture understanding, Teaching Material, Communicative Competence, EFL.